Maternal pre-pregnancy body mass index and newborn telomere length - Martens, Dries S. (BMC Med, 2016)
BACKGROUND: Newborn telomere length sets telomere length for later life. At birth, telomere length is highly variable among newborns and the environmental factors during in utero life for this observation remain largely unidentified. Obesity during pregnancy might reflect an adverse nutritional status affecting pregnancy and offspring outcomes, but the association of maternal pre-pregnancy body mass index (BMI) with newborn telomere length, as a mechanism of maternal obesity, on the next generation has not been addressed. METHODS: Average relative telomere lengths were measured in cord blood (n = 743) and placental tissue (n = 702) samples using a quantitative real-time PCR method from newborns from the ENVIRONAGE birth cohort in Belgium. By using univariate and multivariable adjusted linear regression models we addressed the associations between pre-pregnancy BMI and cord blood and placental telomere lengths. RESULTS: Maternal age was 29.1 years (range, 17–44) and mean (SD) pre-pregnancy BMI was 24.1 (4.1) kg/m(2). Decline in newborn telomere length occurred in parallel with higher maternal pre-pregnancy BMI. Independent of maternal and paternal age at birth, maternal education, gestational age, newborn gender, ethnicity, birthweight, maternal smoking status, parity, cesarean section, and pregnancy complications, each kg/m(2) increase in pre-pregnancy BMI was associated with a −0.50 % (95 % CI, −0.83 to −0.17 %; P = 0.003) shorter cord blood telomere length and a −0.66 % (95 % CI, −1.06 to −0.25 %; P = 0.002) shorter placental telomere length. CONCLUSIONS: Maternal pre-pregnancy BMI is associated with shorter newborn telomere lengths as reflected by cord blood and placental telomeres. These findings support the benefits of a pre-pregnancy healthy weight for promoting molecular longevity from early life onwards. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12916-016-0689-0) contains supplementary material, which is available to authorized users.